The eddy current effect on the transversal sweeping system of a gyrotron collector - Ioannidis, Zisis C.; Tigelis, Ioannis G.; Pagonakis, Ioannis Gr; Illy, Stefan; Schmid, Martin (Plasma Science (ICOPS), 2012 Abstracts IEEE International Conference on, 2012)
Summary form only given. In high-power gyrotrons sweeping systems are used in order to distribute the energy of the spent beam in a larger area of the collector1. Currently, there are two common types of sweeping systems, the axial and transversal sweeping system2. In the first case, the sweeping coils surround the collector creating a harmonically varying magnetic field that is coaxial to the externally applied one. In the second one, the coils are distributed symmetrically around the collector creating a rotating magnetic field normal to the external one. In both cases the periodic variation of the magnetic field induces eddy currents in the conductive walls of the collector, which tend to cancel the magnetic field of the sweeping coils, reducing in this way the efficiency of the sweeping system.
Keywords: Coils; Eddy currents; Educational institutions; gyrotrons; magnetic fields; Materials